MENINGKATKAN HASIL BELAJAR PENDIDIKAN ANTI KORUPSI PADA SISWA KELAS IV MELALUI METODE PROBLEM BASED LEARNING DI UPTD SDN 2 TEGAL OMBO: MENINGKATKAN HASIL BELAJAR PENDIDIKAN ANTI KORUPSI PADA SISWA KELAS IV MELALUI METODE PROBLEM BASED LEARNING DI UPTD SDN 2 TEGAL OMBO - Mufadhilah; Bambang Ariyanto; Misrodin (STKIP Subang, 2026)
ABSTRACT This study aimed to improve students’ learning outcomes in Anti-Corruption Education through the implementation of the Problem Based Learning (PBL) model in Grade IV of UPTD SDN 2 Tegal Ombo. The problem addressed in this study was the low level of students’ learning outcomes caused by conventional teaching methods that limited students’ active participation and their ability to relate learning materials to real-life situations. This research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 15 fourth-grade students in the 2025/2026 academic year. Data were collected through learning outcome tests, observations, and documentation. Data analysis was carried out by calculating the percentage of students’ learning mastery in each cycle. The results showed that the implementation of the Problem Based Learning model significantly improved students’ learning outcomes. Learning mastery in the pre-cycle was only 25%, increased to 53% in Cycle I, and further improved to 87% in Cycle II. In addition to improving learning outcomes, PBL also enhanced students’ activeness, confidence in expressing opinions, and understanding of anti-corruption values in a contextual manner. Therefore, it can be concluded that the Problem Based Learning model is effective in improving learning outcomes in Anti-Corruption Education for elementary school students. Keywords: Learning Outcomes, Anti-Corruption Education, Problem Based Learning, Classroom Action Research. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar Pendidikan Anti Korupsi pada siswa kelas IV melalui metode Problem Based Learning (PBL) di UPTD SDN 2 Tegal Ombo. Permasalahan penelitian ini adalah rendahnya hasil belajar siswa akibat pembelajaran yang masih bersifat konvensional sehingga siswa kurang aktif dan belum mampu mengaitkan materi dengan situasi nyata. Penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, meliputi tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian berjumlah 15 siswa kelas IV tahun pelajaran 2025/2026. Teknik pengumpulan data menggunakan tes hasil belajar, observasi, dan dokumentasi. Analisis data dilakukan dengan menghitung persentase ketuntasan belajar siswa pada setiap siklus. Hasil penelitian menunjukkan bahwa motode Problem Based Learning mampu meningkatkan hasil belajar siswa secara signifikan. Ketuntasan belajar pada pra siklus hanya mencapai 25%, meningkat menjadi 53% pada siklus I, dan kembali meningkat menjadi 87% pada siklus II. Selain meningkatkan hasil belajar, penerapan PBL juga mendorong keaktifan siswa, keberanian menyampaikan pendapat, serta pemahaman nilai-nilai pendidikan anti korupsi secara kontekstual. Dengan demikian, dapat disimpulkan bahwa model Problem Based Learning efektif dalam meningkatkan hasil belajar Pendidikan Anti Korupsi pada siswa sekolah dasar. Kata kunci: Hasil Belajar, Pendidikan Antikorupsi, Problem Based Learning, Penelitian Tindakan Kelas